2003
DOI: 10.1152/ajpheart.00596.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JNK in rat heart by exercise: effect of training

Abstract: The purpose of the study was to determine whether exercise would activate JNK in the heart and whether chronic exercise training would alter the response. Untrained rats were familiarized with the treadmill and assigned to one of four groups: low intensity (LI), 10 min, 0%, 15 m/min; medium intensity (MI), 10 min, 0%, 33 m/min; high intensity (HI), 10 min, 25%, 33 m/min; long duration (LD), 30 min, 0%, 15 m/min. Another cohort of rats was subjected to a progressive 6 wk high-intensity training protocol that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
1
22
0
1
Order By: Relevance
“…Somani and colleagues (49) found that an acute bout of exercise resulted in greater increases of myocardial MnSOD and catalase in previously sedentary rats compared to chronically trained rats even though the acute exercise was more intense for the trained animals. Boluyt and colleagues (50) found greater increases in myocardial c-Jun NH 2 -terminal kinase after exercise in previously sedentary rats compared to their chronically exercised counterparts. Also, in a study investigating the time course of adaptation to a chronic, moderate exercise program, Harris and Starnes (7) observed that changes in antioxidant enzymes occurred during the early phase of the program but returned to sedentary values over time as the animals adapted to the exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Somani and colleagues (49) found that an acute bout of exercise resulted in greater increases of myocardial MnSOD and catalase in previously sedentary rats compared to chronically trained rats even though the acute exercise was more intense for the trained animals. Boluyt and colleagues (50) found greater increases in myocardial c-Jun NH 2 -terminal kinase after exercise in previously sedentary rats compared to their chronically exercised counterparts. Also, in a study investigating the time course of adaptation to a chronic, moderate exercise program, Harris and Starnes (7) observed that changes in antioxidant enzymes occurred during the early phase of the program but returned to sedentary values over time as the animals adapted to the exercise.…”
Section: Discussionmentioning
confidence: 97%
“…Prolonged activation of JNK has been shown to mediate p53-mediated apoptosis, whereas transient activation has been shown to promote cell survival [153]. Aerobic prolonged exercise under one hour modulates energy metabolism by the JNK-regulated balanced interaction between p53 and FOXO activities [154,155]. Thus, instead of selective JNK inhibitors for the treatment of degenerative diseases such as diabetes and Alzheimer's disease [156], future regulators of JNK activity seem much more promising.…”
Section: Conclusion and Therapeutic Impli-cationsmentioning
confidence: 99%
“…It is well known that regular exercise improves CV function (Brown, 2003), in part by activating genes that encode components of contractile elements, metabolic pathways, and protein synthesis (Chen, 2001). Clusters of genes associated with CV energy metabolism and ischemia-reperfusion have been shown to change in an intensity-dependent manner (Boluyt et al, 2003;Iemitsu et al, 2003). Highly trained animals demonstrate healthier CV systems compared to less-trained animals.…”
Section: Introductionmentioning
confidence: 99%